ANALISIS PENGARUH FAKTOR INTERNAL YANG MEMPENGARUHI PENYALURAN KREDIT PADA BANK YANG GO PUBLIK - Tulus Puji Susanti, 11.05.52.0178; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2015)
This study aims to investigate the influence of internal factors on bank lending banks in Indonesia The population in this study is a banking company that is listed on the stock exchange Indonesia 2010-2013. The sample in this study were taken by purposive sampling method. Data were analyzed using normality test, the classical assumption, koofisien determinasi test, F test and test hypotheses. Test results obtained hipotesi that DPK, CAR and LDR significant positive effect on credit, hypothesis testing results obtained that ROA, NPL and ROA significant negative effect on credit.Keywords: DPK, CAR, LDR, ROA, NPL, ROA, CREDIT